Mewujudkan Etika Administrasi Publik dalam Manajemen Pemerintahan Untuk Mewujudkan Pemerintahan yang Bersih dan Bebas dari KKN di Indonesia - Baihaqi, Muhammad Rifqi; Jumiati, Ipah Ema; Kusnadi, Iwan Henri (International Journal of Demos (IJD), 2023)
AbstractÂ Public Administration Ethics as an effort to prevent the emergence of Corruption, Collusion, and Nepotism. Acts of corruption, collusion and nepotism can appear whenever and wherever along the way there is a meeting between intention and opportunity, as has been stated previously. Acts of corruption, collusion and nepotism can occur in both high, middle and low level public bureaucracies. Therefore, to prevent or overcome acts of corruption, collusion, and nepotism in the public bureaucracy, efforts must be made not to reconcile the intentions and opportunities. One of the efforts to prevent the meeting between intentions and opportunities is to uphold and enforce the ethics of Public Administration in the ranks of the public bureaucracy or government. The ethical values of the bureaucracy, as described above, if they really have become a "norm" that must be followed and obeyed by the public bureaucracy in carrying out their duties and authorities, will be able to prevent acts of corruption, collusion, and nepotism in the public bureaucracy. although there is no supervisory agency as mentioned above. However, it is recognized that bureaucratic ethics are not sufficient to ensure that there is no corruption, collusion and nepotism in the bureaucracy. There is the most important thing and the most important thing is to return to the personality of each actor (human). In other words, internal control in the form of faith and religion inherent in humans. They will not commit acts of corruption, collusion, and nepotism when they know and believe that the act is an act that is not good, despicable and not commendable, especially when viewed from the beliefs and religious values they profess. Because all of their attitudes, actions, and behavior must be accounted for later to Allah SWT.Keywords: Public Administration, Ethics, Good GovernanceÂ AbstrakEtika Administrasi Publik sebagai upaya mencegah timbulnya Korupsi, Kolusi, dan Nepotisme. Tindakan Korupsi, Kolusi Dan Nepotisme bisa muncul kapan dan dimanapun sepanjang jalan terjadi pertemuan antara niat dan kesempatan, seperti apa yang telah dikemukakan terdahulu. Tindakan korupsi, kolusi dan nepotisme bisa terjadi baik pada birokrasi publik tingkat tinggi, menengah maupun rendahan. Oleh karenanya untuk mencegah atau mengatasi tindakan korupsi, kolusi, dan nepotisme pada tubuh birokrasi publik harus berupaya untuk tidak mempertemukan antara niat dan kesempatan tadi. Salah satu upaya untuk mencegah tidak bertemunya antara niat dan kesempatan tadi adalah menjunjung tinggi dan menegakkan etika Administrasi Publik pada jajaran birokrasi public atau Pemerintahan. Nilai-nilai etika birokrasi tadi sebagaimana digambarkan diatas, jika betul-betul sudah menjadi suatu â€œnormâ€ yang harus diikuti dan dipatuhi bagi birokrasi publik dalam menjalankan tugas dan kewenangannya, maka akan dapat mencegah timbulnya tindakan korupsi, kolusi, dan nepotisme dalam tubuh birokrasi publik kendatipun tidak ada lembaga pengawasan sebagaimana yang telah disebutkan diatas. Namun diakui, bahwa etika birokrasi tersebut belum cukup untuk menjamin tidak terjadi perilaku korup, kolusi dan nepotisme pada tubuh birokrasi. Terdapat hal yang paling penting dan yang terpenting adalah kembali kepada kepribadian dari masing-masing pelaku (manusianya). Dengan kata lain kontrol internal dalam bentuk keimanan dan keagamaan yang melekat pada diri manusianya. Mereka tidak akan melakukan tindakan korupsi, kolusi, dan nepotisme manakala mereka mengetahui dan menyakini bahwa perbuatan tersebut merupakan suatu tindakan yang tidak baik, tercela dan tidak terpuji terutama jika dilihat dari nilai keyakinan dan keagamaan yang mereka anut. Karena segala dari suatu sikap, perbuatan, dan tingkah laku mereka harus dipertanggungjawabkan kelak kepada Allah SWT.Kata kunci:Â  Etika, Administrasi Publik, Good Governance